2018
DOI: 10.1021/acs.biomac.7b01693
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Self-Assembled Supramolecular Host–Guest Delivery System for Drug Resistant Cancer Therapy

Abstract: In this report, a new star-like copolymer β-CD- g-(PNIPAAm- b-POEGA) , consisting of a β-CD core, grafted with temperature-responsive poly( N-isopropylacrylamide) (PNIPAAm) and biocompatible poly(oligo(ethylene glycol) acrylate) (POEGA) in a block copolymer of the arms, was used to deliver chemotherapeutics to drug resistant cancer cells and tumors. The first step of the self-assembly process involves the encapsulation of chemotherapeutics through host-guest inclusion complexation between the β-cyclodextrin ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 66 publications
0
41
0
Order By: Relevance
“…We found that PEO conjugated to tetraphenylethene (TPE) normally leads to aggregation‐induced emission, and addition of α‐CD leads to a 4–12 fold increase of fluorescence, possibly due to α‐CD restriction on TPE segment rotation . Supramolecular assemblies based on either α‐CD or β‐CD were used in conjunction with cationic copolymer for sustained delivery of Bcl‐2 DNA and combined with temperature‐responsive polymers to deliver the chemotherapeutic paclitaxel ,. Building on the concept of reversible host‐guest complexation, stimuli‐responsive sol‐gel switching materials were designed.…”
Section: Types Of Noncovalent Polymeric Hydrogelsmentioning
confidence: 99%
“…We found that PEO conjugated to tetraphenylethene (TPE) normally leads to aggregation‐induced emission, and addition of α‐CD leads to a 4–12 fold increase of fluorescence, possibly due to α‐CD restriction on TPE segment rotation . Supramolecular assemblies based on either α‐CD or β‐CD were used in conjunction with cationic copolymer for sustained delivery of Bcl‐2 DNA and combined with temperature‐responsive polymers to deliver the chemotherapeutic paclitaxel ,. Building on the concept of reversible host‐guest complexation, stimuli‐responsive sol‐gel switching materials were designed.…”
Section: Types Of Noncovalent Polymeric Hydrogelsmentioning
confidence: 99%
“…This amphiphilic PHB‐based polymer might self‐assembly into nanoparticles and for HepaRG cells uptake, which can be utilized for a feasible drug delivery vehicle . Poly(2‐dimethylamino‐ethyl methacrylate) (PDMAEMA) with thermal sensitivity is often used as block of temperature sensitive drug delivery vehicles . For example, comb‐shaped copolymers made up of 3‐hydroxy‐9‐decenoate (3H9D), or 3‐hydroxydodecanoate (3HDD), with graft of PDMAEMA were utilized for preparing PDMAEMA oligomers with uniform “side chains,” followed by aminolysis at the end of which a sulfhydryl group and final activation of thiol‐containing PDMAEMA.…”
Section: Synthesis Of Polyhydroxyalkanoatesmentioning
confidence: 99%
“…It is well‐known that block copolymer can self‐assemble into distinct domains in selected solvents or in the bulk state . Due to this unique properties, various types of microphase‐separated structures, including cylinders, spheres, lamellae, or gyroids have been reported .…”
Section: Synthetic Strategies Of Polymeric Janus Nanoparticlesmentioning
confidence: 99%